The Influence of Content Marketing and Electronic Word of Mouth on the Purchase Decisions of Shopee Users in the Fashion Segment - Friska Aulia; Fajar Alamsyah, Indra; Estisia Pratiwi, Rizka (UNISBA Press, 2024)
Abstract. Shopee is one of the largest e-commerce platforms in Southeast Asia that offers user-friendly features, various attractive promotions, and reliable services. The platform's popularity attracts numerous visitors, making it the preferred choice for online shoppers. This study investigates the impact of content marketing and electronic word of mouth on purchasing decisions among Shopee users in the fashion segment in Bandung City. The research employed a quantitative method using a survey approach. The study population consisted of Shopee users in Bandung City selected through a purposive sampling technique. A total of 100 respondents were surveyed using an online questionnaire. Data were analyzed using multiple linear regression analysis. The results indicate that content marketing significantly influences purchasing decisions partially, electronic word of mouth also significantly influences purchasing decisions partially, and both content marketing and electronic word of mouth collectively significantly influence purchasing decisions on the Shopee marketplace.